2019
DOI: 10.1213/ane.0000000000004119
|View full text |Cite
|
Sign up to set email alerts
|

New Method of Destroying Waste Anesthetic Gases Using Gas-Phase Photochemistry

Abstract: BACKGROUND: The inhalation anesthetics are potent greenhouse gases. To reduce the global environmental impact of the health care sector, technologies are sought to limit the release of waste anesthetic gas into the atmosphere. METHODS: Using a photochemical exhaust gas destruction system, removal efficiencies for nitrous oxide, desflurane, and sevoflurane were measured at various inlet concentrations (25% and 50%; 1.5%, 3.0%, and 6.0%; and 0.5%, 1.0%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…60 It is possible to destroy both volatile gases and N 2 O with a simple scavenging circuit UV lamp, although the efficiency of removing UV-resistant N 2 O is much less (<10% N 2 O destroyed). 64 Membrane technologies that filter through CO 2 , O 2 and N 2 into the scavenging interface, whilst preventing the larger volatile anaesthetics from escaping into the scavenging stream, are also being actively examined. 65 Anaesthesia scavenging interfaces continuously entrain large air volumes, diluting the WAGs and reducing suitability for effective volatile 'cold trap' condensation.…”
Section: Relevance To the Individual Anaesthetistmentioning
confidence: 99%
“…60 It is possible to destroy both volatile gases and N 2 O with a simple scavenging circuit UV lamp, although the efficiency of removing UV-resistant N 2 O is much less (<10% N 2 O destroyed). 64 Membrane technologies that filter through CO 2 , O 2 and N 2 into the scavenging interface, whilst preventing the larger volatile anaesthetics from escaping into the scavenging stream, are also being actively examined. 65 Anaesthesia scavenging interfaces continuously entrain large air volumes, diluting the WAGs and reducing suitability for effective volatile 'cold trap' condensation.…”
Section: Relevance To the Individual Anaesthetistmentioning
confidence: 99%
“… 54 A recent proof-of-concept study of a photochemical exhaust gas destruction system demonstrated efficient removal of desflurane and sevoflurane, although removal of N 2 O requires further optimization. 55 These and similar strategies provide valuable reductions in the environmental impact of volatile anesthetic gases that can often be implemented in a cost-neutral or even cost-saving fashion. 53 55 …”
Section: Strategies For Environmental and Occupational Improvement: Hospital Anesthesia And Minimization Of Waste And Exposurementioning
confidence: 99%
“… 55 These and similar strategies provide valuable reductions in the environmental impact of volatile anesthetic gases that can often be implemented in a cost-neutral or even cost-saving fashion. 53 55 …”
Section: Strategies For Environmental and Occupational Improvement: Hospital Anesthesia And Minimization Of Waste And Exposurementioning
confidence: 99%
“…Dots present the distribution of raw data for the fraction of time spent spontaneously breathing of even more efficient application systems as well as systems for elimination or recycling of volatile anesthetics may soon diminish ecological concerns. 34 Controlled mechanical ventilation with complete diaphragmatic inactivity for as little as 18-69 h results in marked atrophy of the diaphragm, 5 which impacts clinical outcomes. 6 In contrast, spontaneous breathing reduces dorso-caudal atelectasis and improves cardiac output.…”
Section: Discussionmentioning
confidence: 99%